A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

Le mouvement des femmes québecois: état des lieux - Descarries, Francine (Cités, 2005)
Keywords: OFDIG; amériques; approches et analyses; discours dominant; histoire du féminisme; histoire et politique; justice sociale; militance; mouvements des femmes*; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

A broader vision of the reproductive rights movement: Fusing mainstream and latina feminism - Hooton, Angela (American University Journal of Gender, Social Policy & the Law, 2005)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; femmes* latino-américaines; histoire et politique; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; santé reproductive; science politique et droit; systèmes d'oppressions; thématiques; états-unis